Using lag-sequential analysis for understanding interaction sequences in visualizations. Issue 96 (December 2016) - Pohl, Margit; Wallner, Günter; Kriglstein, Simone
Abstract: The investigation of how users make sense of the data provided by information systems is very important for human computer interaction. In this context, understanding the interaction processes of users plays an important role. The analysis of interaction sequences, for example, can provide a deeper understanding about how users solve problems. In this paper we present an analysis of sequences of interactions within a visualization system and compare the results to previous research. We used log file analysis and thinking aloud as methods. There is some indication based on log file analysis that there are interaction patterns which can be generalized. Thinking aloud indicates that some cognitive processes occur together with a higher probability than others. Abstract : Graphical abstract: Abstract : Highlights: We describe research concerning interaction patterns within visualizations systems. Our results contribute to the understanding of cognitive processes of users. Certain reoccurring patterns can be observed across fairly different visualizations. Analysis was performed using transitional probabilities and lag sequential analysis. Data on interaction sequences was collected using thinking aloud and log-files.